Employer-of-choice branding for knowledge workers - M. M. Sutherland; D. G. Torricelli; R. F. Karg (South African Journal of Business Management, 2002)
Attracting knowledge workers is recognised as a critical success factor by organisations. In order to succeed in the war for talent many organisations realise they need to brand themselves as employers of choice. This research established the factors knowledge workers regard as important organisational attributes when seeking an employer and what communication channels signal these attributes to knowledge workers.This was a two-phase study involving 274 knowledge workers. Qualitative research identified the organisational attributes desired and the communication channels used. Quantitative research using Factor Analysis, Kruskal Wallis and Mann Whitney U tests established the underlying factors, their order of importance and the significant differences in the target market segmentation.The findings show 11 underlying factors, with career growth and challenging work opportunities being the most desired attributes. Word of mouth and/or current employees are the most used communication channels. Differences in the target market were noted by gender, age and cultural groupings. Recommendations are offered for organisations seeking to become employers of choice.
Keywords: 650